Relationship between Personal hygiene and Environmental Sanitation to the Presence of Escherichia coli Bacteria in Food - Erica Ardhana Fathimah Azzahra; Vivi Novianti; Muhammad Al Irsyad (Preventia : The Indonesian Journal of Public Health, 2024)
Food safety is one of the significant public health issues, especially in developing countries. The extraordinary incidence of food poisoning and a high number of cases of gastrointestinal infections in Malang City indicate infection with the bacteria that cause dysentery, namely E.coli. This study evaluated hygiene-sanitation practices at food stalls in Area Terusan Ambarawa Malang City. This study aimed to identify Escherichia coli bacteria in 11 food stalls and assess the relationship of environmental sanitation and personal hygiene of food handlers to the presence of E.coli. This study used a quantitative descriptive design with a cross-sectional approach, data collection using a checklist observation questionnaire sheet, and laboratory tests to determine the number of E.coli bacteria. Based on laboratory tests, 10 (90.1 percent) of 11 food samples exceeded the E.coli quality standard according to the requirements of the Indonesian Ministry of Health Regulation 2023, the results of chi-square analysis of the relationship between environmental sanitation (p is 0.012) and the relationship between personal hygiene (p is 0.012), both variables have a significant relationship to the presence of E.coli. There is a relationship between personal hygiene and environmental sanitation and Escherichia coli contamination in food sold in Area Terusan Ambarawa Malang City.